In-situ boron isotope and chemical composition of tourmaline in the Gyirong pegmatite, southern Tibet: Implications for petrogenesis and magma source - Pei, Qiuming; Ma, Shaobing; Li, Chenghong; Liu, Fei; Zhang, Yunhui; Xiao, Yong; Wang, Shiming; Wu, Jianfei; Cao, Huawen (Frontiers in Earth Science, 2023)
Leucogranitic rocks, mainly including leucogranite-pegmatite systems, have been found to be widely distributed in the South Tibetan Himalaya, and they have received considerable interest because of their significance in crustal evolution and associated rare-metal mineralization. Although the nature and geodynamic setting of the Himalayan leucogranites have been well documented by numerous studies, the pegmatites spatially associated with these leucogranites are still poorly understood. Tourmaline is a ubiquitous phase from the leucogranite to the pegmatite. We have therefore conducted in situ major and trace element and boron isotope investigations of tourmaline from the Gyirong pegmatite, synthesizing published data on Gyirong leucogranite, to document the origin of the tourmaline and its genetic implications. Two types of tourmaline (Tur-Ⅰ & Tur-Ⅱ) have been identified in this contribution and they are enriched in Fe, Si and Al but depleted in Mg and Ca, with Mg/(Mg+Fe) ratios ranging from 0.22 to 0.45. Accordingly, the tourmalines belong to the alkali group and have schorl composition. Trace elements, such as Zn, Ga, V, Sc, Li, Sn, Sr and Co in the tourmalines are relatively enriched, whereas, other trace elements record low concentrations less than 10 ppm. The trace element concentrations of tourmaline are mainly controlled by melt composition. Morphological and geochemical characteristics reflect that the tourmalines from the Gyirong pegmatite are magmatic in origin. The Gyirong pegmatitic tourmalines have S-type granitoids and pegmatites boron isotopic signatures with a tight range of δ11B values between -11.8 and -9.7 ‰, which is consistent with the magmatic tourmalines (Mg-poor) of the Gyirong leucogranite. This study suggests that the Gyirong pegmatite was the product of crustal anatexis and that the crustal metapelitic rocks within the Greater Himalayan Crystalline Complex were the most likely source components.